Pengaruh Investasi, Upah Minimum Kabupaten dan Kunjungan Wisatawan terhadap Penyerapan Tenaga Kerja di Provinsi Bali - Ida Ayu Suci Indrayanti (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
The contribution of the tourism sector in Bali Province has grown over the last twenty years, which can be seen from the number of tourist visits which has increased after the Covid-19 pandemic. The phenomenon that occurs is the gap between tourist visits which increases but the increase in investment and MSEs does not occur in all districts in Bali Province. This research aims to determine whether there is an influence of investment on labor absorption in Bali Province, to determine the effect of district minimum wages and tourist visits on labor absorption in Bali Province. This research was conducted in Bali Province in the 2019-2023 period. The sample in this study used tabular data techniques. The research method uses quantitative descriptive from the results of documentation studies related to investment data, district minimum wages and tourist visits. The results of this research are that there is a positive influence of investment on labor absorption in Bali Province, apart from that there is an influence of the district minimum wage and tourist visits on labor absorption in Bali Province. This research was conducted in Bali Province in the 2019-2023 period.